A Review of the Emergency Medicine Literature on Access to Care (International Journal of Food and Nutritional Sciences, 2022)
The authors examine the development of the emergency medicine literature with regard to access to care and utilisation of emergency departments (ED) over the previous 20 years. They talk about how managed care and cost containment have changed how people think about using emergency rooms. The targeting of nonemergency ED care as a potential source of savings began in the 1980s as a result of the classification of "nonurgent ED visits" as "inappropriate" and high ED charges.The literature discloses numerous initiatives made in the 1990s to recognise "inappropriate" ED visits and to create plans to divert these visits from the ED. By the late 1990s, evidence of the dangers of withholding emergency care and more in-depth evaluations of actual costs had caused measures to restrict access to ED care to be re-examined and a fresh emphasis placed on the crucial function of the ED as a safety net provider. De facto rejections of emergency care as a result of lengthy ED wait times and other negative effects of ED overcrowding have started to predominate the emergency medicine health services literature in recent years. Key words: safety net, emergency department use, access to healthcare, and health services research.